Students’ Attitudes in Learning English for Tourism Using Google Classroom in Mataram Tourism College - Putra, Ida Nyoman Tri Darma (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2020)
The development of information and technology continues to grow in this revolution industry 4.0, especially in the development of technology with the internet. It influences the world of education, especially in learning methods. One of the developments in education and learning methods that are currently in use is Google classroom. The purpose of this study is to identify how students’ responses towards learning English Profession using Google Classroom which is applied to the teaching and learning process at the Mataram College of Tourism. This research is survey research. The number of samples of this study was 135 students from Mataram College of Tourism. The variables examined in this study include aspects of ease in accessing, usefulness, communication and interaction, and studentsâ€™ satisfaction in learning using google classroom. The result of this research shows that students in Mataram Tourism College feel accessing Google Classroom is easy to access, useful, easy for communication and interaction and feel satisfying with Google Classroom. From the interview, the respondents agree that Google Classroom offers helpful features that support the lecturers to manage the course efficiently and effectively. However, from the interview, it was found that the respondents felt that the quality of the learning processing was not better than conventional methods and they were uncomfortable during the learning processing in the google classroom.